Anoxic oxidation of sulphide in bulk water and biofilm phases of municipal sewer / Saliha Mohamad - Mohamad, Saliha (2011)
Anaerobic decomposition of wastewater in sewer systems generates sulphur compounds which leading to the formation of hydrogen sulphide (H2S) has been identified as a major cause of problems related to foul odors, corrodibility and toxicity. Therefore, it is necessary to investigate appropriate techniques and/or technologies for removing H2S. Various studies on the use of nitrate in suppressing sulphide production in sewer systems have been documented. However, limited reports are available on transformation rates of sulphur compounds in sewer systems under anoxic conditions. Lack of this knowledge will prevent estimations of nitrate dosing rates into sewer systems to maintain anoxic condition for sulphide oxidation. Three phases of experiments utilizing anoxic batch reactors were conducted. In phase I, sterilized and active wastewater were used to establish the rates and relative importance of chemical and biological oxidation of sulphide. For Phase II, batch reactors containing bulk water were used to determine the transformation rates of selected sulphur and nitrogen compounds in bulk water phases of municipal sewer. And in phase III, the transformation rates in the biofilm phase were determined using two different batch reactors. One reactor contains both bulk water and biofilm while the other reactor contains only bulk water. Ion Chromatograph (Metrohm 790 IC) was used to analyze concentrations of selected sulphur and nitrogen compounds. Results showed that chemical sulphide oxidation with nitrate were found to be insignificant compared to biological sulphide oxidation process. The median of anoxic biological transformation rates for NO3¯N and NO2¯N were 0.645 and 0.312 mg/L h respectively. The corresponding rates for SO4¯S, SO3¯S and S2O3¯S were determined to be 0.071, 0.000 and 0.049 mg/L h respectively. In bulk water and biofilm phases, sulphate was the end product of anoxic oxidation of sulphide. In bulk water, sulphate being formed at a median rates of 0.103 mg SO4¯S/ (L h) during the 5th to 6th hour and 0.091 mg SO4¯S/(L h) during the 8th to 9th hour. Nitrate, on the other hand was reduced at a median rates of 3.804mg NO3¯N/ (L h) during the 5th to 6th hour and 7.149 NO3¯N/ (L h) during the 8th to 9th hour to nitrogen, with nitrite accumulating at a median rates of 0.856mg NO2¯N/ (L h) during the 5th to 6th hour and 0.934 NO2¯N/ (L h) during the 8th to 9th hour. Based on median value, in biofilm phase sulphate was found to be 0.050 mg SO4¯S / (L h) during the 5th to 6th hour and 0.056mg SO4¯S/ (L h) during the 8th to 9th hour. As for nitrate reduction were 3.582mg NO3¯N/ (L h) during the 5th to 6th hour and 5.198 mg NO3¯N/ (L h) during the 8th to 9th hour. Nitrite accumulation were found to be 0.024 mg NO2¯N/ (L h) during the 5th to 6th hour and 0.088mg NO2¯N/ (L h) during the 8th to 9th hour. Statistical analysis on the relationship between nitrate, nitrite and sulphate in bulk water and biofilm phases under anoxic condition was performed using Pearson correlation analysis. Based on the results, in bulk water phase, insignificant correlations were obtained while in biofilm phase, the significant correlation was obtained for the analysis. Results from this study found that the nitrate compounds can be a good electron acceptor during the anoxic oxidation of sulphide thus removes H2S in sewer systems.